Contribution of gestational diabetes mellitus heterogeneity and prepregnancy body mass index to large‐for‐gestational‐age infants—A retrospective case‐control study. Issue 4 (30th September 2020) - Wang, Ning; Song, Lin; Sun, Bo; Peng, Yanqi; Fei, Sijia; Cui, Jiaqi; Mi, Yang; Cui, Wei
Abstract: Objective: To study the associations between heterogeneity of gestational diabetes mellitus (GDM) subtype/prepregnancy body mass index (pre‐BMI) and large‐for‐gestational‐age (LGA) infants of Chinese women. Methods: We performed a retrospective case‐control study of 299 women with GDM and 204 women with normal glucose tolerance (NGT), using oral glucose tolerance test‐based indices performed at 24‐25 weeks of gestation. Women with GDM were classified into the following three physiologic subtypes: GDM with a predominant insulin‐secretion defect (GDM‐dysfunction), GDM with a predominant insulin‐sensitivity defect (GDM‐resistance), or GDM with both defects (GDM‐mixed). We then used a binary logistic regression model to evaluate the potential associations of GDM subtypes and pre‐BMI with newborn macrosomia or LGA. Results: Women with GDM‐resistance had a higher pre‐BMI ( P  < 0.001), whereas women in the GDM‐dysfunction and GDM‐mixed groups had pre‐BMIs comparable to the NGT group. In the logistic regression model, women in the GDM‐mixed group exhibited an increased risk of bearing newborns with macrosomia and LGA, and women in the GDM‐dysfunction group tended to have newborns with LGA after adjusting for pre‐BMI and other potential confounders. Women who were overweight or obese prepregnancy manifested an increased risk of having newborns with macrosomia and LGA relative to normal‐weight women, regardless of whether values were unadjusted or adjusted for all potential confounders. There was no significant interaction between GDM subtype and pre‐BMI for any of the studied outcomes. Conclusions: Heterogeneity of GDM (GDM‐dysfunction and GDM‐mixed) and prepregnancy overweight/obesity were independently associated with LGA in Chinese women. There was no significant interaction between GDM subtypes and pre‐BMI for LGA. Abstract : Highlights Women with gestational diabetes mellitus (GDM) exhibited heterogeneity based on glycemic physiology. Higher pre‐body mass index (BMI; 24‐27.9 and ≥ 28 kg/m 2 ), GDM‐dysfunction, and GDM‐mixed subtypes were independent risk factors for having large‐for‐gestational‐age (LGA) infants. There was no interaction between GDM‐subtypes and pre‐BMI for macrosomia and LGA infants. 摘要: 目的: 研究中国孕妇中, 妊娠期糖尿病(gestational diabetes mellitus, GDM)异质性分型及孕前体重指数分层(pre‐pregnancy body mass index, pre‐BMI)与大于胎龄儿(large‐for‐gestational‐age, LGA)的关系。 方法: 我们进行了一项回顾性病例对照研究, 我们分析了299例GDM孕妇和204例正常糖耐量(normal glucose tolerance, NGT)孕妇的临床数据。诊断GDM依据妊娠第24‐25周的口服糖耐量试验结果, 按照生理特征将GDM孕妇分为以下三种亚型: 以胰岛素分泌缺陷为主要特征的亚型(GDM‐dysfunction, GDM‐dys), 以胰岛素敏感性缺陷为主要特征的亚型(GDM‐resistance, GDM‐res), 或以上两种特征缺陷均具备的亚型(GDM‐mixed)。使用二元logistic回归模型分析GDM亚型/pre‐BMI与巨大儿或LGA的潜在关联。 结果: GDM‐res组的pre‐BMI较高(P < 0.001), 而GDM‐dys组和GDM‐mixed组与NGT组的pre‐BMI相当。在logistic回归模型中, GDM‐mixed组生产巨大儿和LGA的风险增加, 而校正pre‐BMI和其他潜在混杂因素后, GDM‐dys组生产LGA的风险也增加。与正常孕前体重的孕妇相比, 无论是否调整潜在混在因素, 孕前超重/肥胖的孕妇生产巨大儿和LGA的风险均较高。同时, 本研究未发现GDM各亚型和各pre‐BMI分组之间存在显著的交互作用。 结论: 中国GDM孕妇中, 依据异质性分组, GDM‐dys/GDM‐mixed亚型和孕前超重/肥胖与LGA独立相关。GDM各亚型与pre‐BMI各分组之间对于LGA的影响没有显著的交互作用。